2022
DOI: 10.3390/diagnostics12061384
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Significance of FNAB miRNA Expression in Papillary Thyroid Carcinoma

Abstract: The aim of the study was to evaluate the diagnostic utility of specific miRNAs in the preoperative assessment of thyroid nodules. One hundred and sixty thyroid fine needle aspiration biopsy (FNAB) samples with suspected thyroid carcinoma were collected. To detect the levels of miRNA expression in FNAB, next generation small RNA sequencing was performed in 60 samples. Based on the results obtained, three miRNAs (miR125A, miR200B, miR4324) were selected for further analysis. Based on the most frequently reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Chen et al [59] showed that miR-146b and miR-222 might be used as distinguishing markers for PTC in the material from FNA, but notably they evaluated FNA material obtained ex vivo and the diagnoses were based on surgical pathology reports. Laukien ė et al [60] examined nodules of Bethesda categories III-VI and found that the expression analysis of four miRNAs, miR-55a, miR-146b, miR-221 and miR-4324, improved the accuracy of FNA, but they did not analyze category III BSRTC separately. Keutgen et al [61] evaluated FNA material obtained ex vivo from nodules classified into categories III-V BSRTC jointly and found that the expression of miR-222, miR-328, miR-197 and miR-21 combined in a predictive model was accurate in differentiating malignant from benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [59] showed that miR-146b and miR-222 might be used as distinguishing markers for PTC in the material from FNA, but notably they evaluated FNA material obtained ex vivo and the diagnoses were based on surgical pathology reports. Laukien ė et al [60] examined nodules of Bethesda categories III-VI and found that the expression analysis of four miRNAs, miR-55a, miR-146b, miR-221 and miR-4324, improved the accuracy of FNA, but they did not analyze category III BSRTC separately. Keutgen et al [61] evaluated FNA material obtained ex vivo from nodules classified into categories III-V BSRTC jointly and found that the expression of miR-222, miR-328, miR-197 and miR-21 combined in a predictive model was accurate in differentiating malignant from benign lesions.…”
Section: Discussionmentioning
confidence: 99%